Research on Coherent Stray Light Fringes in Interference Compensation Testing - Yutong Sun; Qiang Cheng; Haixiang Hu; Xin Zhang; Xiaokun Wang; Longxiang Li; Donglin Xue; Xuejun Zhang (Photonics, 2024)
Testing accuracy is an essential factor in determining the manufacturing accuracy of aspheric mirrors. Because of the complexity of the null compensation test, the coherent stray lights generated by multiple reflections and transmissions between optical elements and the crosstalk fringes generated by the multi-beam interference of the reference light, test light, and stray lights are superimposed on the interference fringes, resulting in reduced testing accuracy. Focusing on this problem, a simulation analysis method for crosstalk fringes based on ray-tracing and multi-beam interference in interference testing is proposed. The coordinates, amplitudes, and phases of the test light and stray lights on the transmission sphere are traced, and the crosstalk fringes and interference testing fringes and their positions, sizes, and intensity information are simulated via multi-beam interference. The influence of crosstalk fringes on interference fringes is determined. An experimental optical path is built to verify the correctness of the crosstalk fringe simulation method.